2016
DOI: 10.5194/amt-9-3567-2016
|View full text |Cite
|
Sign up to set email alerts
|

Satellite observation of atmospheric methane: intercomparison between AIRS and GOSAT TANSO-FTS retrievals

Abstract: Abstract. Space-borne observations of atmospheric methane (CH 4 ) have been made using the Atmospheric Infrared Sounder (AIRS) on the EOS/Aqua satellite since August 2002 and the Thermal and Near-infrared Sensor for Carbon Observation Fourier Transform Spectrometer (TANSO-FTS) on the Greenhouse Gases Observing Satellite (GOSAT) since April 2009. This study compared the GOSAT TANSO-FTS thermal infrared (TIR) version 1.0 CH 4 product with the collocated AIRS version 6 CH 4 product using data from 1 August 2010 t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In these studies, the degrees of freedom for signal (DOFS) of the retrieval is significantly lower than 1. Moreover, Zou et al (2016) compared the retrieval of methane profiles from GOSAT and AIRS thermal infrared measurements and observed a prevalent bias at 9 km altitude of about +3 % between both satellite retrievals (AIRS minus GOSAT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, the degrees of freedom for signal (DOFS) of the retrieval is significantly lower than 1. Moreover, Zou et al (2016) compared the retrieval of methane profiles from GOSAT and AIRS thermal infrared measurements and observed a prevalent bias at 9 km altitude of about +3 % between both satellite retrievals (AIRS minus GOSAT).…”
Section: Introductionmentioning
confidence: 99%
“…Currently five nadir-viewing instruments in the thermal infrared are operational on satellite platforms; Atmospheric InfraRed Sounder3816 A. de Lange and J. Landgraf: CH 4 profiles from GOSAT-TIR spectra 2008; Zou et al, 2016); Tropospheric Emission Spectrometer (TES), aboard AURA, launched in 2004 Worden et al, 2012Worden et al, , 2015; Infrared Atmospheric Sounding Interferometer (IASI), aboard Metop-A and Metop-B, launched in respectively 2006 and 2012 (Razavi et al, 2009;Crevoisier et al, 2013;Cressot et al, 2014;Siddans et al, 2017); Thermal and Near infrared Sensor for Carbon Observation -Fourier Transform Spectrometer (TANSO-FTS) aboard the Japanese Greenhouse Gases Observing Satellite (GOSAT), launched in 2009; Cross-track Infrared Sounder (CrIS), aboard Suomi-NPP, launched in 2011 (Han et al, 2013). Furthermore, GOSAT-2, the successor of the GOSAT satellite, will also be equipped with two thermal infrared bands (together covering the same wavelength range as the one TIR band in GOSAT) and a new generation of IASI spectrometers (IASI-NG) will fly on three successive Metop-SG A satellites of the European Organisation for the Exploitation of Meterological Satellites (EUMETSAT) Polar System of Second Generation (EPS-SG) in the 2021-2040 time frame.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for this reason, and because measurements in the TiR are often more uncertain than SWiR measurements, exemplified in multiple studies [56][57][58], we decided to focus on the SWiR in this study. in addition, it has been shown that the SNR on the methane absorption regions in GOSAT are significantly lower than in the SWiR [56,59], suggesting that the This figure is as figure 5 in [27], but has been updated to reflect the use of hiTRAN2016.…”
Section: Tirmentioning
confidence: 99%
“…Grid maps coordinates range from -180.0° to +180.0° in longitude and from -90.0° to +90.0° in latitude [20]. Fifty to sixty bands of CH 4 absorption near (7.66 µm = 1306 cm -1 ) were selected for the CH 4 retrieval, and the atmospheric temperature profiles, water vapor profile, surface temperatures and surface emissivity are required as inputs to compute are derived from other AIRS channels [21].…”
Section: Study Areamentioning
confidence: 99%